Near-miss organizational learning in nursing within a tertiary hospital: a mixed methods study - Tingting Feng; Xin Zhang; Lingling Tan; Yuanyuan Su; Huaping Liu (BMC, 2022)
Abstract Background Near-miss organizational learning is important for perspective and proactive risk management. Although nursing organizations are the largest component of the healthcare system and act as the final safety barrier, there is little research about the current status of near-miss organizational learning. Thus, we conducted this study to explore near-miss organizational learning in a Chinese nursing organization and offer suggestions for future improvement. Methods This was a mixed methods study with an explanatory sequence. It was conducted in a Chinese nursing organization of a tertiary hospital under the guidance of the 4I Framework of Organizational Learning. The quantitative study surveyed 600 nurses by simple random sampling. Then, we applied purposive sampling to recruit 16 nurses across managerial levels from low-, middle- and high-scored nursing units and conducted semi-structured interviews. Descriptive statistics, structured equation modelling and content analysis were applied in the data analysis. The Good Reporting of A Mixed Methods Study (GRAMMS) checklist was used to report this study. Results Only 33% of participants correctly recognized near-misses, and 4% of participants always reported near-misses. The 4I Framework of Organizational Learning was verified in the surveyed nursing organization (χ2 = 0.775, p = 0.379, RMSEA < 0.01). The current organizational learning behaviour was not conducive to near-miss organizational learning due to poor group-level learning (β GG = 0.284) and poor learning absorption (β Misalignment= -0.339). In addition, the researchers developed 13 codes, 9 categories and 5 themes to depict near-miss organizational learning, which were characterized by nurses' unfamiliarity with near-misses, preferences and the dominance of first-order problem-solving behaviour, the suspension of near-miss learning at the group level and poor learning absorption. Conclusion The performance of near-miss organizational learning is unsatisfactory across all levels in surveyed nursing organization, especially with regard to group-level learning and poor learning absorption. Our research findings offer a scientific and comprehensive description of near-miss organizational learning and shed light on how to measure and improve near-miss organizational learning in the future.